A Growing Epidemic: Plastic Surgeons and Burnout—A Literature Review. Issue 2 (August 2019) - Khansa, Ibrahim; Janis, Jeffrey E.
Abstract : Background: The prevalence of burnout is increasing among all physicians, including plastic surgeons. Burnout is not simply synonymous with being overworked. It is a complex physical, intellectual, and psychological entity that arises when the expectation and reality of the job do not match. In this article, the authors' goal is to define burnout, summarize its causes and consequences, and offer the plastic surgeons methods to prevent and address it. Methods: A literature search of articles on burnout in medicine was performed. Articles that were relevant were selected, and were qualitatively analyzed to answer our questions on the definition, prevalence, causes, consequences, and treatments of burnout. Results: Sixty-five relevant articles were included. The prevalence of burnout among physicians ranges between 29 and 55 percent. Risk factors for physician burnout include increased workload and call, junior academic rank, and fair physician health. There is significant overlap among burnout, depression, and substance abuse, and suicide is much more common among physicians than among the general population. Preventing burnout involves a multiprong approach that addresses the physical, intellectual, and psychological dimensions of the physician. Conclusions: In this article, concrete steps to prevent and address burnout are presented to plastic surgeons. For physicians, the most important elements for burnout avoidance are the prevention of emotional exhaustion, and the development of professional autonomy and control. Abstract : For #PRSJournalclub Discussions: Read & Watch Related "Classic" Content and Listen to the Podcast at PRSJournal.com.